Extracellular vesicles as the next‐generation modulators of pharmacokinetics and pharmacodynamics of medications and their potential as adjuvant therapeutics - Jiaqi Liu; Joel Z. Nordin; Andrew J. McLachlan; Wojciech Chrzanowski (Clinical and Translational Medicine, 2024)
Abstract Background and main body Pharmacokinetics (PK) and pharmacodynamics (PD) are central concepts to guide the dosage and administration of drug therapies and are essential to consider for both healthcare professionals and researchers in therapeutic planning and drug discovery. PK/PD properties of a drug significantly influence variability in response to treatment, including therapeutic failure or excessive medication‐related harm. Furthermore, suboptimal PK properties constitute a significant barrier to further development for some candidate treatments in drug discovery. This article describes how extracellular vesicles (EVs) affect different aspects of PK and PD of medications and their potential to modulate PK and PD properties to address problematic PK/PD profiles of drugs. We reviewed EVs' intrinsic effects on cell behaviours and medication responses. We also described how surface and cargo modifications can enhance EV functionalities and enable them as adjuvants to optimise the PK/PD profile of conventional medications. Furthermore, we demonstrated that various bioengineering strategies can be used to modify the properties of EVs, hence enhancing their potential to modulate PK and PD profile of medications. Conclusion This review uncovers the critical role of EVs in PK and PD modulation and motivates further research and the development of assays to unfold EVs’ full potential in solving PK and PD‐related problems. However, while we have shown that EVs play a vital role in modulating PK and PD properties of medications, we postulated that it is essential to define the context of use when designing and utilising EVs in pharmaceutical and medical applications. Highlights Existing solutions for pharmacokinetics and pharmacodynamics modulation are limited. Extracellular vesicles can optimise pharmacokinetics as a drug delivery vehicle. Biogenesis and administration of extracellular vesicles can signal cell response. The pharmaceutical potential of extracellular vesicles can be enhanced by surface and cargo bioengineering. When using extracellular vesicles as modulators of pharmacokinetics and pharmacodynamics, the ‘context of use’ must be considered.